A new approach to determine the optimum tilt angle and orientation of solar collectors in mountainous areas with high altitude. (15th December 2021) - Xu, Luting; Long, Enshen; Wei, Jincheng; Cheng, Zhu; Zheng, Hanjie
Abstract: In mountainous areas with high altitude, abundant sunshine, and low cloud cover presence, the complex terrain is the key factor affecting the spatial and temporal distribution of solar energy. However, at present, when seeking the optimal installation angles of solar collectors in mountainous areas, the terrain shading effect is not fully considered, which seriously restricts the solar energy application. To accurately calculate the optimal angles of solar collectors in mountainous areas with high altitude, the concept of viewshed is introduced in the study to analyze the terrain shading effect quantitatively. By double integrating the solar irradiance over the viewshed, the potential solar irradiation under the terrain shading is predicted to detect the solar collectors' optimal tilt angle and orientation. Then, validation of the method is performed by comparing with the meteorological data of a typical meteorological year and the prediction values of existing radiation models. Besides, Batang county is selected as a case to demonstrate the application of the method. Compared with the recommended angles of the current standard, after considering the terrain shading effect, the optimized annual and monthly optimal angles can increase the solar energy collection by 238.72 kWh/m 2 (9.73%) and 398.33 kWh/m 2 (16.24%) per year respectively. Highlights: Propose a new method to determine optimal angles of solar collectors in high-altitude mountainous areas. Introduce the concept of viewshed to calculate terrain shading effects on solar irradiance. Annual optimal angles can increase yearly radiation collection by 9.73% in Batang. Monthly optimal angles can increase yearly radiation collection by 16.24% in Batang.